The developing sacrum: a new perspective on the relationship between internal architecture and weight transfer - Yusof, Nurul Asyiqin; Soames, Roger W.; Cunningham, Craig; Black, Sue (John Wiley & Sons, Inc., 2014)
This qualitative study examined the pattern of trabecular bone in 76 juvenile sacra from the Scheuer Collection, which is housed in the University of Dundee. The sample spanned from fetal through to late adolescent years. All specimens were X-rayed using macro-radiographic procedures and the images were color mapped using four colors across a spectrum: yellow, violet, orange and blue. The results revealed a constant “chiasmic pattern” passing from the neural arch, across the centrum toward the anterior alae throughout all age ranges including the fetal material, which in utero is not weight bearing. The patterns were more prominent in the infant and prepubertal age group prior to complete fusion of the bone into its final adult form. The relationship between the internal trabecular pattern of the sacrum and its role in body weight transfer through locomotion appears to be related to bipedal milestones.